PENERAPAN DATA MINING UNTUK MEMPREDIKSI PENJUALAN OBAT DI KLINIK HARAPAN KITA BATAM - Hutahaean, Mangaratua; Handoko, Koko (LPPM Universitas Putera Batam, 2022)
Clinics are places or facilities for providing information on drugs and other pharmaceutical supplies to the public. This resulted in uncertain results from sales at the clinic. Types of drugs that are increasingly varied, from drugs that are cheap to prices that if you look at it don't make sense but have very good functions, especially in the distribution of types of drugs. To overcome this problem, the classification of drugs that are sold or not sold at the clinic is based on the variables obtained using the Naive Bayes Agorithm which is able to provide information about the existing products in the clinic and minimize the stock that accumulates for the unsold category. The availability of a lot of data in an area of ​​need for information becomes a reference in making decisions to make business solutions. The desired information in this study is to obtain an accuracy value for the sales data for these drugs, which are often an option. This research uses Rapidminner tools as a medium for testing data to be processed to obtain an ROC (Rank Order Centroid) value of 80% accuracy based on the importance or priority of the criteria.